Exploring the Impact of Music on Mood and Consumer Behavior: A Gender and Age - Based Analysis - Patel, Hetvi; Khakhar, Bhavik; Barvaliya, Ram; Chauhan, Rahul; Maseleno, Andino; Rizal Isnanto, R (Siber Journal of Advanced Multidisciplinary, 2024)
This study explores the relationship between demographic factors—age and gender - and music preferences among a sample of 167 individuals. The analysis reveals a predominantly young population, primarily students, indicating significant implications for understanding music's role in mental health and therapeutic applications. ANOVA results show that Relax Music and Sad Motion exhibit significant differences across age groups, while the Sad Genre and Lyrics Effect reveal significant variations by gender. These findings highlight the importance of tailoring music interventions to specific demographic characteristics. Future research should investigate additional demographic factors and employ longitudinal approaches to deepen insights. This study contributes to the global discourse on music therapy, emphasizing music's potential as a transformative tool for emotional well-being.